2019
DOI: 10.1038/s41598-019-54902-8
|View full text |Cite
|
Sign up to set email alerts
|

Response surface methodological (RSM) approach for optimizing the removal of trihalomethanes (THMs) and its precursor’s by surfactant modified magnetic nanoadsorbents (sMNP) - An endeavor to diminish probable cancer risk

Abstract: Response surface methodology (RSM) approach was used for optimization of the process parameters and identifying the optimal conditions for the removal of both trihalomethanes (THMs) and natural organic matter (NOM) in drinking water supplies. Co-precipitation process was employed for the synthesis of magnetic nano-adsorbent (sMNP), and were characterized by field emission scanning electron microscopy (SEM), trans-emission electron microscopy (TEM), BET (Brunauer-Emmett-Teller), energy dispersive X-ray (EDX) an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
58
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 158 publications
(58 citation statements)
references
References 39 publications
(47 reference statements)
0
58
0
Order By: Relevance
“…Three-dimensional response surface and contour plots ( Figure 4 ) were used to illustrate the interactive effects between four independent variables and the extraction yield of PAs [ 51 ]. The PAs ( z -axis) were plotted against two independent variables while keeping the rest of the variables at a fixed level.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Three-dimensional response surface and contour plots ( Figure 4 ) were used to illustrate the interactive effects between four independent variables and the extraction yield of PAs [ 51 ]. The PAs ( z -axis) were plotted against two independent variables while keeping the rest of the variables at a fixed level.…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, Caco-2 was more sensitive to PAs compared to HepG-2. Kumari and Gupta [ 51 ] reported a marked reduction in probable cancer under RSM optimized conditions. In addition, the mechanistic and preclinical studies demonstrated that the capacity of PAs to modulate the several factors related to colorectal cancer is based on its polymerization degree [ 56 ].…”
Section: Resultsmentioning
confidence: 99%
“…The main objective of response surface methodology is to optimize the response as per the needs of the study. Response surface methodology reduces the number of experiments needed to determine the optimal parameters for the process [30,31]. In the present study, the transesterification process was optimized using response surface methodology to maximize the biodiesel yield, and the influence of the main reaction parameters, including enzyme concentration, oil/alcohol molar ratio, temperature, and time, was investigated.…”
Section: Introductionmentioning
confidence: 99%
“…Response surface methodology (Bingöl 2011;Kumari and Gupta 2019;Abdulgader et al 2020) is used to recognize the optimum combination of the factors and their interactions with minimum effort, which is not possible in the traditional statistical analysis. Levels for different factors are assigned in Table 1.…”
Section: Response Surface Methodologymentioning
confidence: 99%